Fenomena Kawin Muda Di Era Digital Bagi Etnis Karo di Desa Pekan Sawah Kecamatan Sei Bingai Kabupaten Langkat - Septika Meditania Br Ginting; Ratih Baiduri (Jurnal Antropologi Sumatera, 2022)
This study aims to determine the phenomenon of young marriage in the digital era for ethnic Karo in Pekan Sawah Village, Sei Bingai District, Langkat Regency. This research was conducted qualitatively with a descriptive approach. The data needed is collected through observational studies, interviews, and documentation. This research was conducted to determine the phenomenon of young marriage in the digital era for ethnic Karo in Pekan Sawah Village, Sei Bingai District, Langkat Regency. This study concludes that the phenomenon of young marriage in the digital age for the Karo ethnicity in Pekan Sawah Village, Sei Bingai District, Langkat Regency, that the phenomenon of young marriage does not affect every system, because in this case only the most prominent social system. This means that individual behavior in the social system is governed by culture, just as it does in Pekan Sawah Village. They consider young marriages to be commonplace, because previously the village community had done a lot of young marriages. The phenomenon of young marriage that occurs in Pekan Sawah Village is a patterned network, which forms a coherent whole as a totality of social values and their own behavior. The development of technology in the digital direction has brought various changes. The digital age is not a matter of being prepared or not and is not an option but is a consequence.